Prognosis of ulnar neuropathy and ulnar neuropathy-like symptoms in relation to occupational biomechanical exposures and lifestyle - Svendsen, Susanne Wulff; Johnsen, Birger; Fuglsang-Frederiksen, Anders; Frost, Poul (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVE ': 'The aim of this paper was to identify prognostic factors for severity of symptoms and disability among patients with ulnar neuropathy confirmed by nerve conduction studies (NCS) or ulnar neuropathy-like symptoms with normal ulnar nerve NCS. ' ' METHODS ': 'We conducted a cohort study based on a matched case-referent study. In 2008, we mailed a questionnaire to 1179 patients who were examined by NCS for suspected ulnar neuropathy at the age of ≥18–<65 years, 2001–2007. Potential prognostic factors included occupational biomechanical exposures, lifestyle factors, and NCS result. Outcomes were severity of symptoms and disability according to questionnaire scores. Referents delivered reference values. We used ordinal logistic regression. ' ' RESULTS ': 'The percentage of those responding was 61%, comprising 324 patients with ulnar neuropathy and 396 with ulnar neuropathy-like symptoms. At follow-up, both patient groups had more severe symptoms and disability than age and sex matched referents. Abnormal NCS indicated a poorer prognosis regarding symptom severity [odds ratio (OR) 1.44, 95% confidence interval (95% CI) 1.01–2.01], but not disability (OR 0.78, 95% CI 0.57–1.08). High occupational force requirements indicated a poorer prognosis regarding both symptom severity (OR 1.78, 95% CI 1.10–2.88) and disability (OR 1.66, 95% CI 1.06–2.59). Other negative prognostic factors for both outcomes were current smoking, obesity, distal upper-extremity fractures, female sex, and a recent NCS date (suggesting improvement over time). ' ' CONCLUSIONS ': 'NCS confirmation of ulnar neuropathy identified patients with a poorer prognosis regarding symptoms. A negative impact of high occupational force requirements, current smoking, and obesity on both outcomes suggested that reduction of these factors might improve prognosis of ulnar neuropathy and ulnar neuropathy-like symptoms.
Keywords: biomechanical exposure; body mass index; epidemiology; force; job exposure matrix; lifestyle; musculoskeletal disorder; nerve conduction study; posture; prediction model; prognosis; prognostic factor; repetitive work; smoking; ulnar neuropathy; ulnar neuropathy-like symptom; upper extremity